2022
DOI: 10.1002/jso.26811
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced thrombocytopenia and thrombosis in primary lymphedema patients who underwent vascularized lymph node transplantations

Abstract: BackgroundHeparin‐induced thrombocytopenia and thrombosis (HITT) may result in microsurgical flap failure. This study investigated the outcomes of HITT in primary lymphedema patients who underwent vascularized lymph node transplantations (VLNT).MethodsBetween 2012 and 2019, primary lymphedema patients who underwent VLNTs were retrospectively included. The 4Ts score was used to categorize patients into HITT (scores of 5–7) and non‐HITT (score < 5) groups. Outcome evaluations included the re‐exploration rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(258 reference statements)
0
1
0
Order By: Relevance
“…Others have reported that following VLNT, complete normalization of limb volume is achievable in 20% of patients [ 6 ]. Patients with primary lymphedema who undergo VLNT may be at an increased risk of developing heparin-induced thrombocytopenia and thrombosis (HITT), which increases the risk of flap complications [ 50 ]. Case series have suggested that combining VLNT with lipectomy may improve limb circumference and patient satisfaction [ 30 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Others have reported that following VLNT, complete normalization of limb volume is achievable in 20% of patients [ 6 ]. Patients with primary lymphedema who undergo VLNT may be at an increased risk of developing heparin-induced thrombocytopenia and thrombosis (HITT), which increases the risk of flap complications [ 50 ]. Case series have suggested that combining VLNT with lipectomy may improve limb circumference and patient satisfaction [ 30 ].…”
Section: Treatmentmentioning
confidence: 99%